(3HZOGO eOjfI GdSdGe (B:s (3EfTGDgG hJfXje ScGfgG aj GdYghO GdYHGSjI GdChdi (B/s - (3GdYdj, UGdM CMeO,s 1918-2003 ((3HZOGO (B:s (3OGQ GdcJH GdYdejI,s, 2013)
(3jJfGhd cJGH (B((3HZOGO eOjfI GdSdGe (B: (3EfTGDgG hJfXje ScGfgG aj GdYghO GdYHGSjI GdChdj(B) (3hGdPj bGe HJCdjag (B((3UGdM CMeO GdYdj(B) (3aj (B(2 (3eLdO(B) (3ef GdbWY GdeJhSW ehVhY (B((3JGQjN HZOGO(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdbSe GdChd (B: (3GdYhGUe GdChdi ddOQhdI GdESdGejI, GdbSe GdKGfj (B: (3bdH GdeOfjI (B249-259(3, GdbSe GdKGdK (B: (3GdGeJOGO hGdJhSY aj GdCWQGa GdLfhHjI, GdbSe GdQGHY (B: (3GdGeJOGO aj GdTeGd hMOhOg(B.s
(3jTJed Ydi cTGaGJ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B1-2.s
Keywords: (3HZOGOs -- (3JGQjNs